PREVENTION OF MALAIRA IN PREGNANCY (PMIP) – INFORMATION COMPREHENSION, MOTIVATIOIN AND ADHEREANCE AMONGST ANTENATAL CLINIC ATTENDEES IN TARABA, NIGERIA- A DESCRIPTIVE SURVEY. - Alice Garpiya Pibini; Chiegil Solomon; Umeh, Mercy Orji; Iranum Nimiruna; Uriah Danladi; Akilu Hamza; Rachael Abeh Sani; Stephen Maisamari B; Joseph Mohammed Dahmonyi; Grace Christopher Tanko Danjuma (Student's Journal of Health Research Africa, 2023)
Background: